Electrodeposition of tin using tin(ii) methanesulfonate from mixture of ionic liquid and methane sulfonic acid / Yang Kok Kee - Yang, Kok Kee (2010)

(untitled)
The electrodeposition of tin from Tin(II) Methane Sulfonate (MSA) with varying concentration in air and water stable 1-butyl-1-methyl-pyrrolidinium trifluoromethanesulfonate, (BMPOTF) ionic liquid at room temperature was studied. Cyclic Voltammetry served to characterize the electrochemical behavior of tin reduction and oxidation. The diffusion coefficient of stannous ions in the mixture of BMPOTF ionic liquid and MSA based electrolyte obtained via Randles-Sevcik and Cottrell equation was 2 × 10-7 cm2/s. Electroplating on copper panel was conducted under different current densities to determine BMPOTF based tin plating solution current efficiency. Mixture of BMPOTF and MSA based tin plating solution gave current efficiency as high as 99.9%. The deposit morphology of the mixture BMPOTF and MSA based tin coated substrates was observed by using EDX, SEM and AFM. A dense, fine and polygonal grain structure was obtained. BMPOTF based tin plated substrates have shown excellent solderability which was comparable to MSA based coated material in wetting balance test.